STRATEGI KOMUNIKASI PEMASARAN DIGITAL PT. KOMPAS MEDIA NUSANTARA DALAM MENINGKATKAN JUMLAH PAID USERS PORTAL BERITA BERBAYAR Kompas.id - Kurniasari, Putrianti Mungi (Jurnal Visi Komunikasi, 2022)
Online media business competition in Indonesia requires Kompas Daily Newspaper to take efforts to promote Kompas.id. This study aims to find out how digital marketing communication strategy in increasing paid users Kompas.id. This type of research is case study with qualitative approach and in-depth interview data collection techniques. The results concluded that main direction of Kompas.id's digital marketing communication strategy was objective focused in which digital aspects didn’t only appear in the marketing communication mix, but the whole process of the strategy. The steps start from identifying the target audience, designing communication, deciding digital marketing communication mix and it’s channel, determining total budget for digital marketing communication, then measuring the results of digital marketing communication.